Modelos de simulação para análise e apoio à decisão nos processos de corte mecanizado, carregamento e transporte no agronegócio da cana-de-açúcar - BASTOS, Kamyro Jorge José Zaccaria (2009)
In the current days sugarcane occupies an area of approximately 10,5 % of all the Brazilian agricultural land, with an estimated production for the 2008/2009 crop of 528 million t. In the sugarcane production process, the harvest highlights due its high costs, representing approximately 35% of the sugarcane production costs, besides the addition of operational difficulties. In search of solutions that can efficiently coordinate the mechanical cutting, loading and transportation process of sugarcane (STC), the methodology of systems simulations can be applied as a management tool for those processes. This dissertation has the objective of analyzing the technical feasibility of using computer simulation to increase the efficiency of sugarcane delivery, from the harvest to the sucroalcooleira industry. This research was based on the analysis of the following topics: a) computer simulation in agricultural production systems, b) sugarcane mechanized harvest; besides a step based on an empiric and descriptive dissertation part, which was developed with the association of the Jalles Machado Company. It was proposed a computational model, developed on the Stella Software, which allocated the following variables: a) operation filling time, b) operation travel time, c) semi-trailer filling time, d) operation travel time, e) operation transfer time, f) semi-trailer displacement time, g) lock and unlock time, h) time spent in the balance, i) Time spent from displacement to sampling, j) sampling time, k) time to displace to the hyllo , l) toppling time, m) sugarcane weighing on the semi-trailer, n) trucks speed, o) harvesters speed, p) harvesters efficiency, q) sugarcane productivity. Based on the developed models and the simulations performed it can be concluded the sugarcane harvest has a great importance on the sugarcane agribusiness, due the big amount of equipment to be administered, the high costs of the process and to be fundamental to maintain constantly the derivatives productions, such as alcohol, sugar and energy. Therefore, the use of computer simulation has shown to be a very important tool to increase the sugar cane delivery efficiency from the mechanized harvest to the sucroalcooleira industry, allowing testing and supporting decisions on this process management.